Special Education Teachers And Technology: A Metaphor Analysis - Sanal, Seda Ozer (My University, 2022)
In this study conducted within the scope of phenomenology, a metaphor as the participants' perceptions towards technology and the rationale of this metaphor were analyzed. Study data were obtained from 164 special education teachers. The metaphors that special education teachers stated for technology were grouped into four categories: (1) Process, (2) Material, (3) Necessity, and (4) Approach. It has been observed that special education teachers’ perceive technology as a process by attributing its developing, changing, and producing. In the material category, metaphors such as tools, computers, and encyclopedias were frequently conveyed. In the category of necessity, it was emphasized that the teaching process is challenging the teacher and the student, and this challenge is in areas such as following up-to-date developments, receiving additional training, participating in certificate programs, and acquiring personal hobbies. The category of approach included expressing technology as a way of life, a philosophy or a belief.
Keywords: Instructional technology; special education; technology integration; metaphor.